How Much Does a First Folio Cost and How Much is That? - Emma Smith (Journal of Early Modern Studies)
The article attempts a survey of the ways book prices have been conceptualised and deployed as part of bibliography and book history, with a particular focus on Shakespeare’s First Folio. In part it is an attempt to understand the changing prices of books which become valuable through different possible financial heuristics, but its major interest is in the implicit work, both rhetorical and methodological, that is done by conceptions of price, and through analogies and comparisons with what hypothetical book buyers might also buy or earn. The period in which rare books were invented as a consumer category is the period of wealth created by the trade in enslaved people and in goods produced by enslaved people: this differently freighted comparison brings out the ethical and conceptual problems raised in discussions of historic book prices.